Effect of Spirulina on Lipid Profile, Glucose and Malondialdehyde Levels in Type 2 Diabetic Patients - Azmand Rostami, Hormat Alsadat; Marjani, Abdoljalal; Mojerloo, Mohammad; Rahimi, Behdad; Marjani, Majid (Univ Sao Paulo, Conjunto Quimicas, 2022)
The study aimed to assess possible spirulina effects on lipid profile, glucose, and malondialdehyde levels in new cases of type 2 diabetes. The subjects consisted of 30 new cases of types 2 diabetes that divided into two groups; each consisted of 15 diabetic patients. Group I did not take any functional food or supplement and received no spirulina supplementation. Group II or experimental group also did not take any functional food or supplement but received spirulina supplementation. Analysis of data was done using SPSS 16.0. The Kolmogorov-Smirnov test, paired West, Wilcoxon test, and Spearman correlation analysis were used to analyze the data. After eight weeks of spirulina supplementation, significant differences were shown in the serum levels of total cholesterol, low-density lipoprotein (LDL)-cholesterol, triglyceride, and malondialdehyde. The serum fasting blood glucose, lipid profiles, and malondialdehyde levels at baseline were negatively and positively correlated with changes in these parameters. Spirulina supplementation may have a beneficial effect on lipid profile and malondialdehyde (MDA) levels through an interventional 8 weeks. This effect may protect subjects against free radicals and the development of some diseases such as atherosclerosis. The spirulina supplementation also showed a potential lipid-lowering effect on new case type 2 diabetic patients which may help the diabetics to have control on lipid levels. In addition, spirulina may be used as a functional food for the management of lipid profiles and MDA levels.
Keywords: Spirulina; Glucose; Lipids; Malondialdehyde; Diabetes Mellitus; Type 2